A Critical Interpretation on Ancient Methodology of Shava Shanrakshana (Cadaver Preservation) According to Acharya Sushruta - Kumar, Rajeev; Kumar, Sujit (International Research Journal of Ayurveda & Yoga, 2024)
In the ancient Indian culture little evidence is present in Hindu’s mythological and Ayurvedic Samhita’s and Grantha. In the Ramayana chapter Ayodhya Kanda evidence of Body preservation is mentioned about 5000 BC ago and in the Ayurvedic Classics in Sushruta Samhita of the body preservation is described and as earlier as first give the concept of preservation of cadaver and selection of cadaver. The Need for Preservation was for Long before early practitioners of medicine in India began dissecting cadavers to study the human body. The Ancient Egyptians also believed that the preservation of the mummy empowered the soul after death, which would return to the preserved cadaver. The Ancient Egyptians (3200 BC) believed that the preservation of the mummy empowered the soul after death. In the 19th and early 20th centuries, arsenic was frequently used as an embalming fluid but has since been supplanted by other more effective and less toxic chemicals.